Konsep Pemasaran Islam pada Unit Usaha Pesantren “Gambia Department Store” - Izzati, Sayyida Alya; Wahyudi, Amin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Islamic marketing is marketing that focuses on creating value and optimizing benefits based on honesty, justice, openness, and sincerity in accordance with the principles of transactional agreements in Islam. Gambia Department Store is one of the cottage business units that should apply the concept of Islamic marketing and Islamic values of the cottage in terms of marketing. The research method used in this research is field research with a qualitative approach. The data collection technique uses interviews and observations. While the data analysis uses inductive analysis. The purpose of this research is to find out the suitability between the marketing concept applied by Gambia Department Store with the 7P's Islamic marketing concept and to find out the Islamic values of the cottage applied by the managers of Gambia Department Store in its marketing activities. The result of this research is that Gambia Department Store has implemented Islamic marketing concept based on Islamic teachings. This is evidenced by the conformity between the marketing concept applied by Gambia Department Store and the integration of the 7P's Islamic marketing concept. In addition, Gambia Department Store also applies Islamic values in the marketing activities carried out, such as the value of honesty, discipline, order and sincerity of the staff and employees in the management and marketing of the goods in Gambia Department Store.